Acid-Unlocked Two-Layer Ca-Loaded Nanoplatform to Interfere With Mitochondria for Synergistic Tumor Therapy - Zheng Y; Williams GR; Hu R; Tong S; Xu J; Wang T; Zhang Y; Wu J; Li F; Cai Y; Zhu LM (International Journal of Nanomedicine)
Yilu Zheng,1 Gareth R Williams,2 Ran Hu,1 Sen Tong,3 Jianxiang Xu,1 Tong Wang,1 Yanyan Zhang,1 Junzi Wu,3 Fan Li,4 Yingyu Cai,4 Li-Min Zhu1 1College of Biological Science and Medical Engineering, Shanghai Engineering Research Center of Nano-Biomaterials and Regenerative Medicine, Donghua University, Shanghai, 201620, People’s Republic of China; 2UCL School of Pharmacy, University College London, London, WC1N 1AX, UK; 3The Key Laboratory of Microcosmic Syndrome Differentiation, Education Department of Yunnan, Yunnan University of Chinese Medicine, Kunming, 650500, People’s Republic of China; 4Department of Ultrasound, Shanghai General Hospital, Shanghai Jiao Tong University School of Medicine, Shanghai, 201620, People’s Republic of ChinaCorrespondence: Yingyu Cai, Department of Ultrasound, Shanghai General Hospital, Shanghai Jiao Tong University School of Medicine, Shanghai, 201620, People’s Republic of China, Email yingyu.cai@shgh.cn Li-Min Zhu, College of Biological Science and Medical Engineering, Shanghai Engineering Research Center of Nano-Biomaterials and Regenerative Medicine, Donghua University, Shanghai, 201620, People’s Republic of China, Email lzhu@dhu.edu.cnBackground: The development of selective formulations able to target and kill tumor cells without the application of external energy has shown great promise for anti-tumor therapy.Methods: Here, we report a “nanobomb” that explosively increases Ca content within cells. It can selectively release Ca2+ and generate H2O2 in the tumor microenvironment (TME) by acid-triggered degradation of the two-layer protective shell (ie, unlocking the “double-lock”). This material, termed CaO2@ZIF8:CUR@PAA, comprises a CaO2 core coated with the ZIF-8 framework, which was then loaded with curcumin (CUR) and coated again with polyacrylic acid (PAA).Results: Under the slightly acidic conditions of the TME, the PAA shell (first lock) breaks down first exposing CaO2@ZIF8 and CUR inside the cell. Then, ZIF8 (second lock) is degraded in response to acid to deposit Ca2+, and H2O2. CUR can promote the release of Ca2+ from the endoplasmic reticulum to the cytoplasm, inhibit the outflow of Ca2+, and accumulates a large amount of Ca2+ intracellularly together with exogenous Ca2+ (calcium storms). The powerful calcium storm that causes mitochondrial dysfunction. The presence of a large amount of exogenous H2O2 causes further oxidative damage to tumor cell membranes and mitochondria where intracellular ROS production far exceeds clearance. CaO2@ZIF8:CUR@PAA NPs can induce cell S cycle arrest and apoptosis to inhibit tumor multiplication and growth. Oxidative damage-triggered immunogenic cell death (ICD) in turn leads to the polarization of macrophages to the M1 phenotype, inducing immunogenic cell death and inhibiting tumor cell proliferation and metastasis.Discussion: The acid two-step unlocking nanoplatform is a therapeutic modality that combines calcium storm and oxidative damage. The mode triggers apoptosis leading to ICD of tumor cells. The material induces cycle blockade during treatment to inhibit cell proliferation. Robust in vitro and in vivo data demonstrate the efficacy of this approach and CaO2@ZIF8:CUR@PAA as an anticancer platform, paving the way for nanomaterials in immune-triggered cancer therapy.Highlights: - A new calcium accumulation nanoplatform plays a role in activate antitumor immunity.- Double-locked structure slows down the premature decomposition of CaO2.- The platform allows Ca2+ and H2O2 to accumulate in tumor cells.- This leads to mitochondrial dysfunction, apoptosis, and M1 macrophage polarization.- Potent anti-tumor effects are seen both in vitro and in vivo.Keywords: Calcium ion load, controlled-release nanomaterials, two-layer protective shell, pH responsive drug release, reactive oxygen species, anti-cancer